AB0641 The Role of Oro-Pharyngeal-Esophageal Scintigraphy in The Evaluation of The Swallowing Function in Patients with Idiopathic Inflammatory Myopathies: Short-Term Results of An Ongoing Prospective Study. (15th July 2016) - Barsotti, S.; Puccini, G.; Tripoli, A.; Talarico, R.; Volterrani, D.; Mosca, M.; Neri, R.; Grosso, M.
Abstract : Background: Dysphagia represents a major burden in IIM patients. OPES is a safe, reliable and repeatable technique, which allow a semi-quantitative scoring of oropharyngeal (OP) and esophageal (E) involvement. OPES is widely used in neuromuscular diseases and could replace other traditional imaging techniques, such as esophageal x-ray, which is difficult to repeat, allows only qualitative examination and exposes patients to risk of aspiration pneumonia. Objectives: The primary aim of our study was to explore prevalence of upper gastrointestinal abnormalities in IIM using OPES. Secondary aim was to correlate the presence of alterations detected by OPES with disease activity and dysphagia in IIM patients. Methods: Twenty-eight IIM patients were enrolled (M:F=3:25; 11 dermatomyositis, 15 polymyositis, 2 inclusion body myositis; mean age: 60±14.7 years; mean disease duration: 52±44 months). Each patient underwent a disease activity evaluation: physician's and patients' visual analogue scale (phVAS and ptVAS), health quality assessment questionnaire, manual muscle test 8 (MMT8) and serum creatine kinase. Dysphagia was assessed by a validated patients reported outcome questionnaire, the "MD Anderson dysphagia inventory" (MDADI), which classifies dysphagia as not present, mild, moderate, severe and total disability. Dysphagia parameters, assessed by OPES after 10 ml liquid (L) or semi-solid (SS) bolus labelled with 99mTechnetium-nanocolloid intake, were: pre-deglutition penetration, aspiration, OP and E transit time and retention index (RI). OP-RI was classifiable by a 4 grade scale: no retention (<8% of the swallowed bolus), mild (9–20%), moderate (21–40%) and severe retention (>40%), while E-RI was classifiable by a 3 grade scale: no retention (<20%), mild (20–45%) and severe retention (>45%). Results: According to MDADI score, 10 patients (36%) presented no dysphagia, 12 (43%) mild, 4 (14%) moderate and 2 (7%) severe disability. OPES showed a normal OP and E transit time in all patients. OP-RI or E-RI were altered in almost all patients, and, both after L and SS bolus, RI was altered in 25 patients. In the 10 patients with no dysphagia symptoms, IR alterations for L and SS bolus were detected respectively in 9 and 7 patients. Correlations with statistical significance between disease activity parameters and MDADI index were found for phVAS and ptVAS ( p =0.032 and p =0.017) and MMT8 ( p =0.014), while E-RI correlated with MMT8 ( p =0.007). Moreover, 13 patients presented uncoordinated movement at proximal and medium esophagus and 2 patients presented SL bolus inhalation. No patients presented pre-deglutition penetration. Conclusions: Dysphagia represents a major disabling feature in 64% of IIM patients and is associated with disease activity. From the clinical point of view, OPES allows to identify subclinical involvement in almost all patients examined, even if no symptoms were reported by the patients. Greater sample size and, above all, prospective clinical follow-up will clarify the clinical meanings of the alterations detected by OPES and their prognostic value. Disclosure of Interest: None declared